2021
DOI: 10.1038/s41598-021-03356-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seaweed extracts on in vitro rumen fermentation characteristics, methane production, and microbial abundance

Abstract: Several seaweed extracts have been reported to have potential antimethanogenic effects in ruminants. In this study, the effect of three brown seaweed species (Undaria pinnatifida, UPIN; Sargassum fusiforme, SFUS; and Sargassum fulvellum, SFUL) on rumen fermentation characteristics, total gas, methane (CH4), carbon dioxide (CO2) production, and microbial populations were investigated using an in vitro batch culture system. Seaweed extract and its metabolites, total flavonoid and polyphenol contents were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…For example, Ma et al (47) reported that supplementation with natural polyphenol resveratrol reduced the total VFA content regardless of the diet type or fermentation time. Our previous study also showed that supplementation with brown seaweed extracts (with similar or lower contents of flavonoids and polyphenols than those in red seaweed extracts) decreased the abundance of proteolytic species (13). However, different types of flavonoid and polyphenol compounds are produced in different seaweed species, explaining their different effects on the rumen microbiota (13).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, Ma et al (47) reported that supplementation with natural polyphenol resveratrol reduced the total VFA content regardless of the diet type or fermentation time. Our previous study also showed that supplementation with brown seaweed extracts (with similar or lower contents of flavonoids and polyphenols than those in red seaweed extracts) decreased the abundance of proteolytic species (13). However, different types of flavonoid and polyphenol compounds are produced in different seaweed species, explaining their different effects on the rumen microbiota (13).…”
Section: Discussionmentioning
confidence: 94%
“…The capability of seaweed to contribute wellbeing and health in livestock is mediated by bioactive compounds that are synthesized by a few seaweed species (8)(9)(10)(11). Some of these bioactive compounds [e.g., bromoform in red species and polyphenols or phlorotannins in brown species (12)(13)(14)] are associated with a reduction in methanogenesis in the rumen. Many seaweed species have been evaluated through in vitro studies, and some have been shown to reduce CH 4 production Abbreviations: AANC, Amphiroa anceps; ATAX, Asparagopsis taxiformis; CTEN, Chondracanthus tenellus; GELL, Grateloupia elliptica; GPAR, Gracilaria parvispora; CE, Catechin equivalent; GAE, garlic acid equivalent; PCoA, principal coordinate analysis; LDA, linear discriminant analysis; LEfSe, linear discriminant analysis e ect size; KEGG, Kyoto encyclopedia of genes and genomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methane is strongly believed to contribute to global warming and climate change because methane has 23 to 25 times more global warming potential than carbon dioxide [ 1 ] Apart from the industrial processes, the livestock sector emerges as the largest source of methane emissions from the agricultural sector because methane from farm animals accounted for 38% of the greenhouse gases produced [ 2 ], in which ruminants contribute to approximately 90% of the greenhouse gas emissions [ 3 ]. Moreover, in the ruminal fermentation process, 2–15% of ingested gross energy is converted to methane [ 4 ]. Therefore, making every effort to inhibit the methane production from ruminants not only can improve feed efficiency, but also mitigate the greenhouse effects and bring outstanding environmental advantages [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the ruminal fermentation process, 2–15% of ingested gross energy is converted to methane [ 4 ]. Therefore, making every effort to inhibit the methane production from ruminants not only can improve feed efficiency, but also mitigate the greenhouse effects and bring outstanding environmental advantages [ 4 ]. Gut methane is produced by methanogenic archaea as a byproduct of feed fermentation and is eructated as waste from the animal into the atmosphere [ 5 ].…”
Section: Introductionmentioning
confidence: 99%